Performance Analysis of Mesh Network Implementation Using Mikrotik RouterBoard 941 in Radio Link-Based Secure Networks - Riska Andian Turnip; Kitu Gea; Yoga Pramadio Purba; Rasme Kita Kaban; Sumarlin; Ita Margaretta Br Tarigan (Karya Techno Solusindo, 2026)
The increasingly rapid development of computer network technology demands a network system that is reliable, flexible, and able to adapt to dynamic environmental conditions. One of the network technologies that is currently developing is mesh networking. Mesh networking is a network topology where each node can be connected to each other directly or indirectly through other nodes. This research aims to analyze the application of the mesh networking method using the Mikrotik RouterBoard 941 device. The research method used is experimental by configuring, implementing, and testing mesh networking on the Mikrotik RouterBoard 941. The results of the research show that mesh networking can be applied to the Mikrotik RouterBoard 941 by utilizing available features, such as OLSR (Optimized Link State Routing) and WDS (Wireless Distribution System). Mesh networking is able to increase redundancy and network availability, and can adapt to changes in network topology. However, mesh networking also has several disadvantages, such as configuration complexity, routing overhead, and the possibility of bottlenecks at certain nodes. REFERENCES Adiguna, M. A. (2022). WPA2-PSK network security analysis using penetration testing method (Case study: TP-Link Mercusys MW302R router). Anhar. (2020). Jaringan komputer dan internet. Informatika. Athailah. (2020). Bandwidth management in optimizing the use of Mikrotik routers for network connection services. Journal of Informatics, 7(2), 70–78. Brown, S. (2021). Computer network development system. McGraw-Hill. Cisco Networking Academy. (2020a). Introduction to networks: OSI model. Cisco Press. Cisco Networking Academy. (2020b). The application of virtual local area network. Journal of Electrical Engineering Innovation, 1(1), 70–80. Danniel. (2021). Comparison of IPv4 and IPv6 in building networks. International Journal of Computer Networks, 3(2), 30–40. Efendi, M. Y. (2021). Comparative analysis of 128-bit WEP and WPA wireless security methods to improve wireless security. Journal of Information Security, 5(1), 10–18. Goldsmith, A. (2020). Wireless communications. Cambridge University Press. Hamacher, V. C. (2020). Decision-making model under complex picture fuzzy Hamacher aggregation operators. Journal of Intelligent Systems, 9(8), 47–68. Harefa, M. F. (2021). User data security applications and wireless security systems using two-factor authentication and MAC address filtering. Journal of Computer Security, 4(1), 20–28. Harmayani, H., Abdilah, D., Mapilindo, M., Oktopanda, O., & Hutahaean, J. (2021). Aplikasi komputer. Yayasan Drestanta Pelita Indonesia. Heart, A. (2020). Analysis and implementation of Mikrotik router security system from Winbox exploitation, brute-force, and DoS attacks. Jurnal Media Informatika Budidarma, 4(1), 57–59. Jackson, M. (2020). Hierarchical network design-based network security system design. International Journal of Network Security, 5(8), 1–9. John, A. (2021). Analysis and application of Mikrotik RB890. Journal of Network Engineering, 2(6), 50–60. Kamila, M. (2024). Design and construction of practicum module simulation of microwave link installation on mobile systems based on virtual reality technology. Kozierok, C. M. (2021). The TCP/IP guide: A comprehensive, illustrated internet protocols reference. No Starch Press. Madcoms. (2020). Network security implementation using port blocking and port knocking methods on Mikrotik RB941. Journal of ICT: Information Communication & Technology, 5(1), 16–17. Michael, J. (2021). OSI model fundamentals. Computer Networks Journal, 1(5), 1–8. Molisch, A. F. (2021). Wireless communications (2nd ed.). Wiley. Prayoga, J. (2021). Comparison of WPA2 EAP-PSK authentication system on wireless networks using penetration testing method with fluxion tools. Journal of Cyber Security, 3(1), 1–10. Permatasari, U. S., & Widiasari, I. R. (2020). Analisis routing protokol optimized link state routing (OLSR) pada Raspberry Pi. Jurnal Teknologi Informasi (AITI), 16(2), 151–164. Primaned, A., Widyawan, W., & Kusumawardani, S. S. (2014). Unjuk kerja routing protocol OLSR pada wireless mesh network berbasis IEEE 802.11b/g. Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 1(1), 8–12. Defri, E. O., Kusmaryanto, S., & Mustofa, A. (2019). Implementasi jaringan access point dengan wireless distribution system (WDS) berbasis Mikrotik. Jurnal Mahasiswa Teknik Elektro Universitas Brawijaya, 7(7). Politeknik Sawunggalih Aji. (2021). Rancang bangun wireless mesh network menggunakan routing OLSR. Jurnal Nasional Teknik Informatika, 9(2). Sofana, I. (2021). Jaringan komputer berbasis TCP/IP. Informatika. Stevens, W. R. (2020). TCP/IP illustrated (Vol. 1). Addison-Wesley. Supendar, H., & Handrianto, Y. (2017). Simple queue in resolving bandwidth management issues on the Mikrotik bridge. Bina Insani ICT Journal, 4(1), 21–30. Sutiono. (2020). Sistem keamanan jaringan. Deepublish. Tanenbaum, A. S., & Wetherall, D. J. (2020). Computer networks (5th ed.). Pearson. Wheeb, A. H., Nordin, R., Samah, A. A., & Kanellopoulos, D. (2023). Performance evaluation of standard and modified OLSR protocols. Electronics, 12(6), 1334. Widiyawati, S. (2020). Network security system firewall using port blocking and firewall filtering methods. Journal of Information Security, 5(2), 78–96. Wirano, B. (2020). Policy analysis from formulation to implementation. Deepublish.